Radiomics-Based Features for Prediction of Histological Subtypes in Central Lung Cancer - Li, Huanhuan; Gao, Long; Ma, He; Arefan, Dooman; He, Jiachuan; Wang, Jiaqi; Liu, Hu (Frontiers in Oncology, 2021)
Objectives: To evaluate the performance of radiomic features on classifying histological subtypes of central lung cancer in contrast-enhanced CT (CECT) images. Materials and Methods: A total of 200 patients with radiologically defined central lung cancer were recruited. All patients underwent dual-phase chest CECT, and the histological subtypes (adenocarcinoma (ADC), squamous cell carcinoma (SCC), small cell lung cancer (SCLC)) were confirmed by histopathological samples. 107 features were used in five machine learning classifiers to perform the predictive analysis among three subtypes. We trained and validated models in two conditions: only using radiomic features, and combing clinical features with radiomic features. The performance of the classification models was evaluated by the area under the receiver operating characteristic curve (AUC). Results: The highest AUCs in classifying ADC vs. SCC, ADC vs. SCLC, and SCC vs. SCLC were 0.879, 0.836, 0.783, respectively by using only radiomic features by feedforward neural network. Conclusion: Our study indicates that radiomic features based on the CECT images might be a promising tool for noninvasive prediction of histological subtypes in central lung cancer and the neural network classifier might be a preferred choice to this task.